Neurological disease associated with Mycoplasma pneumoniae infection. PCR evidence against a direct invasive mechanism. Issue 1 (February 1995) - Fink, C G; Sillis, M; Read, S J; Butler, L; Pike, M
Abstract : Aims —To investigate the pathology in patients presenting with sudden onset neurological illnesses associated with Mycoplasma pneumoniae infection. Methods — M pneumoniae infection was diagnosed by a highly rigorous interpretation of serological markers initially using complement fixation, agglutination and IgM antibodies. Confirmation of the serological diagnosis was achieved using indirect immunofluorescence for IgM, IgA, and IgG. Serum and cerebrospinal fluid (CSF) samples from these patients were examined using the polymerase chain reaction to look for evidence of M pneumoniae DNA. Results —No M pneumoniae DNA was found in any serum or CSF samples. Diagnosis of M pneumoniae infection by agglutination and complement fixation antibodies was not always confirmed by indirect immunofluorescence. Conclusion —The neurological lesions in these patients do not appear to be caused by the direct invasion of M pneumoniae into the nervous system. The lesions may be an immune response to infection. Serological diagnosis of M pneumoniae continues to be a laboratory problem.